Sustainable Crop Production Recent Advances - Singh Meena, Vijay; Choudhary, Mahipal; Prakash Yadav, Ram; Kumari Meena, Sunita (IntechOpen, 2022)
Sustainable Crop Production - Recent Advances addresses various nutrient, crop, and soil management issues, including recent advances in sustainable food production in the context of the changing climate. Chapters present case studies on long-term field experiments in specific locations with a focus on the state of the art of sustainable agriculture production systems.